ANTI-INFLAMMATORY ACTIVITY OF KNEMA ATTENUATA (HOOK. F. AND THOMSON) WARB ETHANOLIC STEM BARK EXTRACT IN ALBINO WISTAR RATS - SUPRIYA RAJA H (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Knema attenuata (Myristicaceae), popularly known as “wild nutmeg,” is an endemic tree species from Western Ghats, which has been used in folk medicine. Conventionally, the stem bark of K. attenuata is used for treating inflammatory conditions without any scientific information available for the same. The present study was undertaken to evaluate the anti-inflammatory activity of the ethanolic stem bark extract (ESBE) of K. attenuata using in vivo and in vitro screening models. Methods: The ethanolic extract of stem bark was prepared by soxhlation, and its cytotoxicity in RAW 264.7 cell line was assessed using MTT assay method. In vivo anti-inflammatory effect of extract was estimated in rats using carrageenan-induced paw edema model and cotton pellet-induced granuloma model. The in vitro anti-inflammatory activity of the extract was evaluated by cyclooxygenase and lipoxygenase inhibition assay, estimation of myeloperoxidase activity, and determination of cellular nitrite levels in lipopolysaccharide-stimulated RAW 264.7 macrophage cells. Results: Toxic symptoms were not observed for the ESBE. The extract demonstrated significant anti-inflammatory activity in both in vivo and in vitro models. The anti-inflammatory action exhibited by the extract was a result of the inhibition of leukocyte migration and nitric oxide pathway and partially by inhibition of mediators such as prostaglandins and leukotrienes. Conclusion: Findings from the study provide the evidence for the popular use of stem bark extract of K. attenuata as a potential anti-inflammatory agent.